Uncertainty Shocks in a Model of Effective Demand - Basu, Susanto; Bundick, Brent (Econometrica, 2017)
This paper examines the role of uncertainty shocks in a one-sector, representative-agent dynamic stochastic general-equilibrium model. When prices are exible, uncertainty shocks are not capable of producing business-cycle comovements among key macro variables. With countercyclical markups through sticky prices, however, uncertainty shocks can generate uctuations that are consistent with business cycles. Monetary policy usually plays a key role in osetting the negative impact of uncertainty shocks. If the central bank is constrained by the zero lower bound, then monetary policy can no longer perform its usual stabilizing function and higher uncertainty has even more negative eects on the economy. Calibrating the size of uncertainty shocks using uctuations in the VIX, we nd that increased uncertainty about the future may indeed have played a signicant role in worsening the Great Recession, which is consistent with statements by policymakers, economists, and the nancial press.